Impact of solid content in the electrospinning solution on the physical and chemical properties of polyacrylonitrile (PAN) nanofibrous mats - Grothe, Timo; Storck, Jan Lukas; Dotter, Marius; Ehrmann, Andrea (Tekstilec)
Polyacrylonitrile (PAN) belongs to the group of polymers that are often used for electrospinning, as it can be applied as a pre-cursor for carbon nanofibers and is spinnable from the low-toxic solvent dimethyl sulfoxide (DMSO). While the influence of different spinning parameters on fibre morphology and mass per unit area was investigated in a previous study, here we report on the impact of the spinning solution, using DMSO as a solvent and wire-based (needleless) electrospinning. Our results show that a broad range of solid contents can be applied, providing the opportunity to tailor the fibre diameter distribution or to optimize the areal weight of the nanofibrous mat by changing this parameter, while the chemical composition of the fibres remains identical.
Keywords: needleless electrospinning; polyacrylonitrile (PAN); nanofibrous mat; dimethyl sulfoxide (DMSO); Fourier-transform infrared (FTIR) spectroscopy